Developing Assessment using the TaRL Approach with the PjBL Model on the Topic of Global Warming - Listyaningrum, Trisna Avi; Kusumaningtyas, Dian Artha; Toifur, Moh. (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2024)
This research addresses the limitations of existing physics assessments that primarily focus on outcomes and cognitive abilities, neglecting the need for a deeper understanding of global warming. The study aims to develop assessments using the teaching at the right level (TaRL) approach with a projectbased learning (PjBL) model specifically for global warming. It follows a Research and Development (R&D) methodology using the ADDIE method, comprising analysis, design, development, implementation, and evaluation stages. The developed assessments undergo validation by experts and physics teachers, followed by a limited trial involving 36 tenthgrade students. Questionnaires, observation sheets, and validation sheets are utilized, and data analysis is performed using descriptive qualitative methods with scoring criteria. The findings reveal that the assessments consist of both formative and summative components, covering various aspects such as diagnostic assessments, learning process evaluations, and project assessments. Expert validation confirms the high suitability of the assessment content and components, with an average score of 3.77 from all validators. Consequently, it is concluded that the TaRL approach with the PjBL learning model for global warming assessments is highly suitable for student use.